Analisis Konektivitas Wilayah di Kota Denpasar - Aprilia Riszi Indah Dewi Shara (Universitas Pendidikan Ganesha, 2018)
Connectivity analysis is one of the most important things in a regional planning or development. A certain region can be developed properly if the connectivity system of the region is good too. The aim of this research is to identify regional hierarchy, service centers, and inter-regional interactions in each sub-district in Denpasar City. The method used in this research is quantitative method. Data analyzed by using index analysy of centrality, gravitation model, and konig-shimbel. The results showed that based on centrality index and gravity model, West Denpasar District has the highest value compared to the other three districts in Denpasar City. It shows that West Denpasar District is an area with hierarchy I (growth center) Denpasar City. Determination of hinterland-center of Denpasar is based on the availability of facilities in each sub-district. Keywords: connectivity, hierarchy areas, Denpasar City